Preservation Potential and Microbial Growth Inhibitory Effect Of Galangal (Alpinia galanga (L.) Willd.) And Lemongrass (Cymbopogon citratus (DC.) Stapf) Oils And Extracts On Chicken (Gallus domesticus) Fillets - Hartanti, Dwi; Pradani, Dea Yulinestria; Nurlaeli, Eli; Fadlilah, Intan Nur; Syah Putri, Tina; Djalil, Asmiyenti Djaliasrin; Hamad, Alwani (Media Farmasi, 2024)
Galangal (Alpinia galanga (L.) Willd.) and lemongrass (Cymbopogon citratus (DC.) Stapf) are spices known for their antimicrobial activity and potentially developed into a natural food preservative. This study evaluated the potential development of galangal and lemongrass oils and extracts for natural food preservatives. The essential oils and water extracts of galangal and lemongrass were obtained by water and steam distillation and infusion methods, respectively. Chicken fillets were immersed in three concentrations of galangal and lemongrass oils and extracts, with sterile water as the control. The fillets were tightly closed, kept in the refrigerator for 15 days, and evaluated for their preservation potential and microbial inhibitory activity on days 3, 6, 9, 12, and 15. The chicken fillet preservation potential was evaluated by comparing the time spoilage signs started to be observable in the control and treatment groups. The percent of microbial growth inhibition (%MI) was calculated from optical density (OD) and was used as the antimicrobial activity parameter. The %MI was analyzed by two-way ANOVA at α=0.05. Treatment and storage time significantly affected %MI. Galangal extracts at 10 and 20% delayed rancid odor, off-texture, and slime formation for nine days. Microbial growth inhibitory activity was shown by galangal oil at 0.25, 1.25, and 6.25 mg/ml and galangal extract at 20%. In conclusion, galangal extract at 20% was the most promising sample potentially developed into a natural chicken fillet preservative.